Distribution of target site PPO-inhibiting herbicide resistance mutations in waterhemp and Palmer amaranth and association of epyrifenacil efficacy with PPX2 target site variants - Jacob Montgomery; Daljit Singh; Andrew Tyre; Jaishree Chittoor; Clifford Wollam; Brandi Chiapelli; John Pawlak; Chandrashekar Aradhya; Alejandro Perez-Jones (Weed Technology, 2025)
During the 2019 growing season, seeds of Palmer amaranth and common waterhemp were collected from 141 and 133 agricultural sites, respectively, from across the southeastern and midwestern United States. These accessions were screened with a new protoporphyrinogen oxidase (PPO) inhibitor, epyrifenacil, using a whole-plant bioassay at 20 g ai ha−1 in controlled environmental conditions to estimate its efficacy on these two agronomically important weeds. In addition, the coding sequence of the PPX2 gene was determined for plants from each accession through short-read sequencing of cDNA fragments amplified via polymerase chain reaction. Results showed that nearly all accessions were completely controlled by epyrifenacil, with average survival rates of less than 2% for both species. Target site resistance mutations toward PPO inhibitors were lower in Palmer amaranth (<20%) compared to waterhemp, with nearly half of all waterhemp samples (42%) possessing the ΔG210 allele, which is shown to cause high-level resistance to other commercially available PPO-inhibiting herbicides. Follow-up testing of accessions with high frequency (≥50%) of the ΔG210 allele of PPX2 compared the efficacy of epyrifenacil, saflufenacil, and saflufenacil + trifludimoxazin and showed that of the herbicides tested, epyrifenacil at 20 g ha−1 provided the best control, averaging 85% mortality across these accessions. Same-plant association study of molecular data and whole-plant assay correlated all detected variants of PPX2 with visual injury following epyrifenacil treatment and found that the ΔG210 mutation was associated with a reduction in relative efficacy of epyrifenacil in some accessions. All other known target site resistance mutations appeared to have no significant effect on epyrifenacil efficacy.